Organoleptic testing of coconut midrib ash and alcohol as preservatives of insect specimens - Hasan Maulana; Yossa Istiadi; Dolly Priatna (Indonesian Journal of Applied Environmental Studies, 2020)
This study uses a Completely Randomized Design experimental method (CRD) consisting of three treatments with a range of 5 days, 10 days and 15 days, with each treatment uses three insect specimens. The treatments in this study were; P1 (200 mg ash + 200 ml distilled water), P2 (70% alcohol), and P0 (control). To observe the changes in texture, aroma and color in the inspect specimens, 50 panelists were engaged, who were aged between 17-30 years, that were not color blind and/or reporting any ill health at the time of sampling. Panelists observed the specimens for texture, aroma and color.  Resulting data was analyzed using t test, frequency tabulation, histogram data and normality test. The texture testing treatments yielded tcount = 0.02521 (p 0.05) showing no significance between the coconut midrib ash and alcohol preserved samples, with the Ho accepted, so there is no difference in the texture of insect specimens preserved in either coconut midrib ash or alcohol. The aroma test resulted in tcount = 0.00908 (p 0.05) showing again there was no significant difference between insect specimens preserved in coconut midrib ash and alcohol. Thus, the Ho can be accepted, with no difference in the aroma of insect specimens preserved in coconut midrib ash or with alcohol. The color test resulted in a tcount = 0.05635 (p 0.05), giving a insignificant result between insect specimens preserved in coconut midrib ash or alcohol. Thus, the Ho can be accepted, and there is no difference in color of insect specimens preserved with coconut midrib ash or those preserved with alcohol. From the overall results and analysis, we can conclude there is no difference in the quality insect specimens preserved either by coconut midrib ash and alcohol for a maximum 15 days. Penelitian ini menggunakan metode eksperimen rancangan acak lengkap (RAL) yang terdiri dari tiga perlakuan dengan kisaran lama waktu 5 hari, 10 hari, dan 15 hari. Setiap satuan percobaan menggunakan tiga spesimen serangga, perlakuan dalam penelitian ini meliputi P1(200 mg abu + 200 ml aquades), P2 (alkohol 70%), dan P0(kontrol). Parameter yang diamati mengenai tekstur, aroma dan warna. Untuk mengamati perubahan tekstur, aroma dan warna yang terjadi, dilakukan oleh 50 orang panelis yang berusia antara 17-30 tahun dengan kriteria tidak buta warna dan tidak sedang dalam keadaan sakit. Data yang diperoleh dianalisis dengan menggunakan uji t, tabulasi frekuensi, data histogram dan uji normalitas. Berdasarkan hasil penelitian, pengujian tekstur  menghasilkan nilai thitung  = 0,02521 (p 0,05), diperoleh hasil yang tidak berbeda secara signifikan antara perlakuan dengan abu pelepah kelapa dan alkohol terhadap tekstur spesimen serangga. Dengan demikian dapat disimpulkan bahwa tidak terdapat perbedaan tekstur spesimen serangga yang diawetkan dengan abu pelepah kelapa dengan yang diawetkan dengan alkohol.  Pengujian aroma menghasilkan nilai thitung= 0,00908 (p 0,05), diperoleh hasil tidak berbeda secara signifikan antara perlakuan dengan abu pelepah kelapa dan perlakuan dengan alkohol. Dengan demikian dapat disimpulkan bahwa tidak terdapat perbedaan warna spesimen serangga antara yang diawetkan dengan abu pelepah kelapa dengan yang diawetkan dengan alkohol. Dari hasil pengamatan dapat disimpulkan bahwa tidak ada perbedaan kualitas antara specimen serangga yang diawetkan dengan abu pelepah kelapa dengan yang diawertkan dengan alcohol dalam waktu maksimum 15 hari.